2020
DOI: 10.1002/jmd2.12130
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of phenylketonuria and tetrahydrobiopterin deficiency in Jordan

Abstract: Background Information regarding the prevalence of PKU in the Middle East in comparison to other world regions is scarce, which might be explained by difficulties in the implementation of national newborn screening programs. Objective This study seeks for the first time to genotype and biochemically characterize patients diagnosed with hyperphenylalaninemia (HPA) at the Pediatric Metabolic Genetics Clinic at the King Hussein Medical Center, Amman, Jordan. Methods A total of 33 patients with HPA and 55 family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…The frequency of PCD deficiency in the present study was 7.1%, exceeding the 2.6% reported in BIODEFdb (BIODEFdb), which could suggest that the frequency of the different BH4 disorders varies among populations ( Souza et al, 2018 ; Carducci et al, 2020 ; Bozaci et al, 2021 ; Gundorova et al, 2021 ; Ray et al, 2022 ). We only found one homozygous c.289G > A or p.(Glu97Lys) male patient.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…The frequency of PCD deficiency in the present study was 7.1%, exceeding the 2.6% reported in BIODEFdb (BIODEFdb), which could suggest that the frequency of the different BH4 disorders varies among populations ( Souza et al, 2018 ; Carducci et al, 2020 ; Bozaci et al, 2021 ; Gundorova et al, 2021 ; Ray et al, 2022 ). We only found one homozygous c.289G > A or p.(Glu97Lys) male patient.…”
Section: Discussioncontrasting
confidence: 86%
“…We are also a tertiary medical referral center for symptomatic patients suspected to have inborn metabolic diseases. In other populations with a high prevalence of BH4D, a high incidence of consanguinity or endogamy (57%) has been found as a possible explanation ( Carducci et al, 2020 ); remarkably, in the present study, there was a lower proportion of families with consanguinity or endogamy (4/14 families, 28.5%, Table 4 ). Moreover, the hypothesis of a founder effect for the c.331G>T or p.(Ala111Ser) variant in the southeastern region of Mexico ( Fernández-Lainez et al, 2018 ), could not be demonstrated here, but further studies are warranted in a larger number of patients.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The first PKU screening project in Jordan was initiated in collaboration with the Ministry of Health (MOH) in 2006. The MOH in Jordan began the NBS program for PKU, congenital hypothyroidism (CH) in 2008, and Favism (G6PD-deficiency) in 2012 for all newborns, including Syrians and refugees from other countries [11]. Furthermore, we have only one specialized clinic in Jordan to monitor and treat PKU patients.…”
Section: Introductionmentioning
confidence: 99%